Adolf Eichmann se tornando um psicopata: um estudo psicanalítico - Klain, Wilson (2020)
The aim of this paper is to investigate, in the light of Psychoanalysis, the factors that led Otto Adolf Eichmann, a young man from a German middle family, to become the “architect” of the Final Solution, and therefore responsible for the murder of thousands of people during the Nazi rule. The study begins by examining some elements of German history since its founding, seeking to find the ingredients that may have contributed to the consolidation, in psychoanalytic terms, of a personality suited to the Nazi project. For this, historical facts regarding the foundation of that country are presented as cultural factors that corroborated the Germanic “spirit”, as well as the presence of the myth of the “Aryan race”. Psychoanalytic theory is called upon to contribute with the concepts of introjection and identification, in order to support the understanding of the importance of these factors as ingredients of the culture surrounding the young Eichmann. For this he is presented at various times, which will allow us to observe the formation of his personality from childhood, until becoming one that is associated with the extermination of six million Jews. Nazism, as a totalitarian proposal, is here understood as a harmonic note to these elements present in culture and, therefore, will be demonstrated as a something that potentiate pre-oedipal factors, as proposed by Psychoanalysis. Eichmann’s last years in Argentina will be presented as confirmation of his personal purposes often disguised by ideology. Eichmann’s discussion of psychopathy will be illustrated by the analysis of two characters from the literature – Hamlet and Ricardo III – examined by Freud in two of his works on the subject.